2003
DOI: 10.1007/s10040-002-0241-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of hydromechanical coupling in fractured rock engineering

Abstract: This paper provides a review of hydromechanical (HM) couplings in fractured rock, with special emphasis on HM interactions as a result of or directly connected with human activities. In the early 1960s, the coupling between hydraulic and mechanical processes in fractured rock started to receive wide attention. A series of events-including dam failures, landslides, and injection-induced earthquakes-were believed to result from HM interaction. Moreover, the advent of the computer technology in the 1970s made pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
363
1
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 576 publications
(374 citation statements)
references
References 127 publications
5
363
1
5
Order By: Relevance
“…[14] Most hydromechanical models have been developed from laboratory experiments and describe fracture hydromechanical behavior as a function of normal stress [Rutqvist and Stephansson, 2003]. Because of the difficulties in developing laboratory measurement facilities for shear-slip experiments, only a few models have been proposed for understanding fracture hydromechanical behavior under shear stress [Makurat et al, 1990;Olsson and Barton, 2001].…”
Section: Fracture Elastic Hydromechanical Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Most hydromechanical models have been developed from laboratory experiments and describe fracture hydromechanical behavior as a function of normal stress [Rutqvist and Stephansson, 2003]. Because of the difficulties in developing laboratory measurement facilities for shear-slip experiments, only a few models have been proposed for understanding fracture hydromechanical behavior under shear stress [Makurat et al, 1990;Olsson and Barton, 2001].…”
Section: Fracture Elastic Hydromechanical Behaviormentioning
confidence: 99%
“…Fluid flow in such fractured rock is often complex because of heterogeneities, both at the scale of the single fracture and the entire fracture network. Numerous laboratory, field, and modeling investigations have shown that fluid flow in a single deformable fracture can depend on a number of factors such as the fracture hydraulic and mechanical parameters, the effective stresses applied on the fracture plane, the amount of surface contact area and voids, and channeling [Rutqvist and Stephansson, 2003]. For example, any variation in stress on fracture changes the geometry of its void space, which in turn changes its global permeability and preferential flow paths [Pyrak-Nolte and Morris, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hopkins et al [61] show that joint normal stiffness in laboratory samples can vary over several orders of magnitude, along with the percentage of contact area within the joint. On a larger scale, measurements of fault aperture in the field have shown that a shear offset results in an undulating pattern of variable fracture aperture [44,62]. Faults would then be represented better with a variable width of void space and a variable contact area, to take into consideration the variability of hydraulic aperture and normal stiffness [17][18]23,63].…”
Section: Heterogeneity Of Fracture Hydromechanical Propertiesmentioning
confidence: 99%
“…These naturally occurring discontinuities often form complex, hierarchical networks over a broad range of length scales, and dominate the bulk behaviour of geological media (Bonnet et al 2001). It is, therefore, important to understand and characterise the distribution of natural fractures in geological formations, which is relevant to a variety of engineering applications such as hydrocarbon extraction, geothermal production, groundwater remediation and geological disposal of radioactive waste (Rutqvist and Stephansson 2003;Lei et al 2017).…”
Section: Introductionmentioning
confidence: 99%